The outcome of third stage of labor using carbetocin following vaginal delivery - Jahan, Mahbuba Akhter; Ashraf, Fatema; Bhuiyan, Shah Mohammad Ashek Uddin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Primary postpartum hemorrhage (PPH) is a major cause of morbidity and the leading cause of direct maternal death worldwide. Carbetocin, a synthetic analog of oxytocin, has an elimination half-life of 40 minutes compared with 10 minutes for oxytocin, Methods: This cross-section observational study was conducted at the department of obstetrics and gynaecology, Shaheed Suhrawardy medical college hospital, Dhaka, Bangladesh. The study period was from May 2016 to October 2016. 100 women undergoing normal vaginal delivery were the study subject. A convenient sampling technique was used in this study. Necessary data was collected in the data collection sheet. A standardized deliver mat (Quaiyum's mat) was used before placental removal for measuring blood loss. Carbetocin was an intervention in this study. Statistical analysis was carried out by using the statistical package for social sciences version 19.0 for Windows (SPSS Inc., Chicago, Illinois, USA). The mean values were calculated by frequencies and percentages. Result: In this study, the majority 54 (54.0%) of patients belonged to age 20-25 years, followed by 30, (30.0%) >25 years. Regarding the occupational status of the patients, it was observed that the majority of 92 (92.0%) patients were housewives. It was observed that the majority of 93 (93.0%) patients had regular menstrual history. Concerning the clinical indices, anaemia was found 69 (69.0%), jaundice 08 (8.0%) and edema 24 (24.0%). Primi para was found 59 (59.0%) and multipara was 41 (41.0%). Primigravida was found 08 (8.0%) and multigravida was 92 (92.0%). In this study, 76 (76.0%) patients had spontaneous delivery, 05 (5.0%) patients had massive blood loss, and 10 (10.0%) patients required further massage. Conclusions: Carbetocin appears to be an effective new drug in the active management of third-stage labor (AMTSL). A single dose (100 mg) of IV carbetocin is more effective for maintaining adequate uterine tone.